Perceived value of satisfaction with services provided to faculties among liaison librarians - Abu Bakar, Ahmad Bakeri (University Malaya, 2009)
This study examines the changes in the way the information services are delivered to the faculty. One of the delivery methods for the faculty adopted by most academic libraries in Malaysia is putting in place a liaison programme. Generally, online resources have made faculty less reliant on the partnership under the programme for help with teaching and research, while electronic communication, such as e-mail, with the library has the potential to make the partnership more lasting and effective. Under this programme, a reference librarian is appointed as a liaison librarian for each Faculty to which he/she is responsible. The study revealed that the liaison librarians have no choice but to upgrade their competencies which they lack in order to perform their responsibilities up to the expected level of excellence demanded by the faculty. They must promote, collaborate and maintain good rapport with the faculty.